THE FREQUENCY AND MANAGEMENT OF INTESTINAL TUBERCULOSIS; A HOSPITAL BASED STUDY - Arif, Atta Ullah; Shah, Liaqat Ali; Ullah, Asad; Sadiq, Muzaffar ud Din (Journal of Postgraduate Medical Institute, 2011)
Objective: To determine the frequency of clinical manifestation of intestinal tuberculosis and outcome of different treatment modalities. Material and Methods: This descriptive study was conducted at Lady Reading Hospital Peshawar from July 2005 to June 2006. Fifty cases having radiological evidence of tuberculosis in the intestines were included in the study. Various parameters like age, sex, presentation, investigation and various treatment modalities were studied. Results: Twenty three (46%) patients presented with subacute and 13 (26%) with acute intestinal obstruction and 12 (24%) with signs of peritonism. Presenting symptoms were: pain abdomen and anorexia in 47(94%) patients, nausea / vomiting in 30 (60%) patients and constipation in 28 (56%) patients. Tenderness was present in 48 (96%) patients and distension of abdomen in 35 (70%). Two (4%) patients were treated conservatively and 48 patients (96%) were managed by surgery (emergency surgery 34 cases, semi-elective surgery 14 cases). In 47 (94%) patients, diagnosis was confirmed by characteristic caseating granuloma. Resection of the small bowel with ileo-ileal anastamosis was done in 16 cases and limited right hemicolectomy with ileo-colic anastamosis in 14 cases. Two staged procedures were performed in 8 cases. Only three (6%) cases needed re-admission for complications, two (4%) for sub-acute obstruction and one (2%) for ileostomy prolapse. Conclusion: Abdominal tuberculosis presents with pain abdomen, anorexia, vomiting and with signs of intestinal obstruction. The surgical procedures like resection with primary anastomosis have satisfactory outcome. Two stage surgical procedures are advisable if the risk of anastamotic leakage and faecal fistula formation is high.